Cancer Patients, Cancer Pathways
XII, 270 p.
Keywords: Eleven essays by historians and sociologists examine cancer research and treatment as everyday practice in post-war Europe and North America. These are not stories of inevitable medical progress and obstacles overcome, but of historical contingencies, cultural differences, hope, and often disappointed expectations.